SC75741, A Novel c-Abl Inhibitor, Promotes the Clearance of TDP25 Aggregates via ATG5-Dependent Autophagy Pathway - Zhou, Dongheng; Yan, Huanhuan; Yang, Shuying; Zhang, Yuhong; Xu, Xiaoyan; Cen, Xufeng; Lei, Kai; Xia, Hongguang (Frontiers in Pharmacology, 2021)
Abnormal accumulation of TDP43-related mutant proteins in the cytoplasm causes amyotrophic lateral sclerosis (ALS). Herein, unbiased drug screening approaches showed that SC75741, a multi-target inhibitor, inhibited inflammation-induced aggregation by inhibiting NF-κB and also degraded already aggregated proteins by inhibiting c-Abl mediated autophagy-lysosomal pathway. We delineate the mechanism that SC75741 could markedly enhance TFEB nuclear translocation by an mTORC1-independent TFEB regulatory pathway. In addition, SC75741 enhanced the interaction between p62 with TDP25 and LC3C, thus promoting TDP25 degradation. Taken together, these findings show that SC75741 has beneficial neuroprotective effects in ALS. Our study elucidates that dual-targeted inhibition of c-Abl and NF-κB may be a potential treatment for TDP43 proteinopathies and ALS.